Correction: Pickering-emulsion-templated synthesis of 3D hollow graphene as an efficient oil absorbent. Issue 49 (17th September 2021) - Pohan, Nurul Aqilah; Wahid, Mohd Haniff; Zainal, Zulkarnain; Ibrahim, Nor Azowa
Abstract : Correction for 'Pickering-emulsion-templated synthesis of 3D hollow graphene as an efficient oil absorbent' by Nurul Aqilah Pohan et al., RSC Adv., 2021, 11, 3963–3971. DOI: ; 10.1039/D0RA09265G .